Designs of two randomized, community-based trials to assess the impact of influenza immunization during pregnancy on respiratory illness among pregnant women and their infants and reproductive outcomes in rural Nepal - Tielsch, James M (BMC Pregnancy Childbirth, 2015)
BACKGROUND: Among the most important causes of illness and death in both pregnant women and their newborn infants are respiratory infections including influenza. Pregnant women in North America have a 4 to 5 fold excess rate of hospitalization compared to non-pregnant women. Rates of infant hospitalization associated with influenza are much higher than in their mothers. Fully half of children hospitalized for influenza in the US are in the age group 0–5 months, a group where no vaccine is licensed. Data on influenza are much fewer in low income countries where the risks of serious morbidity and mortality are much higher. A recent trial in Bangladesh suggested that influenza immunization in pregnant women could have important protective effects against influenza in both mothers and their infants. These trials were designed to provide additional evidence about the effect of influenza vaccination in pregnancy in settings where influenza may circulate for up to ten months/year. METHODS/DESIGN: We conducted a consecutive pair of community-based, placebo-controlled, randomized trials of influenza vaccination of pregnant women in a rural district in southern Nepal. Two trials were conducted to insure, as much as possible, the match of circulating strains with those included in the vaccine. Eligible women included all who were or became pregnant over a one year period. Each trial included a one year cohort of pregnant women who were individually randomized to the influenza vaccine available at the time of their enrollment or placebo. Exclusions included a history of allergy to vaccine components, prior influenza vaccine receipt, and for the second trial, participation in the first trial. Morbidity was assessed on a weekly basis for women throughout pregnancy and through 180 days post-partum. Infants were followed weekly through 180 days. Primary outcomes included: 1) incidence of influenza like illness in women, 2) incidence of laboratory confirmed influenza illness in infants, and 3) birthweight among newborn infants. DISCUSSION: We have presented the design and methods of two randomized trials of influenza immunization of pregnant women. TRIAL REGISTRATION: Clinicaltrials.gov: (NCT01034254).